Trypanosomatid phosphoglycerate mutases have multiple conformational and oligomeric states - Blackburn, Elizabeth A.; Ahmad Fuad, Fazia Adyani; Morgan, Hugh P.; Nowicki, Matthew W.; Wear, Martin A.; Michels, Paul A.M.; Fothergill-Gilmore, Linda A.; Walkinshaw, Malcolm D. (ELSEVIER, 2014)
Three structurally distinct forms of phosphoglycerate mutase from the trypanosomatid parasite Leishmania mexicana were isolated by standard procedures of bacterial expression and purification. Analytical size-exclusion chromatography coupled to a multi-angle scattering detector detected two monomeric forms of differing hydrodynamic radii, as well as a dimeric form. Structural comparisons of holoenzyme and apoenzyme trypanosomatid cofactor independent phosphoglycerate mutase (iPGAM) X-ray crystal structures show a large conformational change between the open (apoenzyme) and closed(holoenzyme) forms accounting for the different monomer hydrodynamic radii. Until now iPGAM from trypanosomatids was considered to be only monomeric, but results presented here show the appearance of a dimeric form. Taken together, these observations are important for the choice of screening strategies to identify inhibitors of iPGAM for parasite chemotherapy and highlight the need to select the most biologically or functionally relevant form of the purified enzyme.